PERAN LITERASI KEUANGAN SYARIAH DALAM MEMPERKUAT PENGARUH RELIGIUSITAS ISLAM TERHADAP TINGKAT ADOPSI PERBANKAN SYARIAH DI INDONESIA - Nanang Setiawan; Thorida Nur Asih; Fitria Asas; Afif Safrudin; Moch Sulchan (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2026)
The development of Islamic banking in Indonesia has demonstrated significant growth; however, its adoption rate remains relatively low despite the country’s predominantly Muslim population. This study aims to examine the role of Islamic financial literacy in strengthening the influence of Islamic religiosity on the level of Islamic banking adoption in Indonesia. The study employs a quantitative research design using a survey approach of 292 Muslim university students who are customers of Islamic banks in Indonesia, with data analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that Islamic religiosity has a positive and significant effect on the level of Islamic banking adoption. Furthermore, Islamic financial literacy is found to function as a moderating variable that strengthens the relationship between Islamic religiosity and Islamic banking adoption. This study introduces a novel perspective by positioning Islamic financial literacy as a reinforcing mechanism in the relationship between Islamic religiosity and Islamic banking adoption behavior. Theoretically, this study contributes to the Islamic finance literature by enhancing understanding of the interactive role of religiosity and financial literacy in explaining the adoption behavior of Islamic financial services. Practically, the findings provide important implications for Islamic banks and regulators in designing more targeted Islamic financial education and literacy strategies to increase the adoption of Islamic banking in Indonesia Keywords : Sharia financial literacy, Islamic religiosity, Islamic banking adoption